An ion exchange mediated shape-preserving strategy for constructing 1-D arrays of porous CoS1.0365 nanorods for electrocatalytic reduction of triiodide1. Issue 15 (21st April 2015) - Patil, Supriya A.; Shinde, Dipak V.; Lim, Iseul; Cho, Keumnam; Bhande, Sambhaji S.; Mane, Rajaram S.; Shrestha, Nabeen K.; Lee, Joong Kee; Yoon, Tae Hyun; Han, Sung-Hwan
<x xml:space="preserve">Abstract</x> A solution based ion exchange mediated strategy for constructing 1-D arrays of porous CoS1.0365 nanorod film from analogous 1-D array of Co3O4 film derived from pyrolysis of nanostructured cobalt hydroxycarbonate film.